Muallaf - Yasmin Ahmad, 1958-2009; Sheikh Munasar ([Kuala Lumpur] : MHz Film Sdn Bhd., 2008)
Two Malaysian sisters, Rohani and Rohana, run away from home to escape their wealthy father's mistreatment. They find refuge in a small town where they get to know Brian Goh, a young Catholic school teacher. Brian is irresistibly attracted to the two girls. Impressed by their extraordinary courage in the face of adversity, their relationship forces him to confront the ghosts of his own childhood
Title from container
Bonus: the making of muallaf; theatrical trailer ; theatrical trailer
Executive producer, Ahmad Puad Onah
Cast: Brian Yap, Sharifah Amani, Shrifah Aleysha, Tony Savarimuthu
DVD format
Language tracks in English, Malay and Chinese; with Malay, English or Chinese subtitles
Keywords: Sisters -- Drama; Muslim converts from Christianity -- Drama; Friendship -- Drama; Psychic trauma -- Drama